T-DNA characterization of genetically modified 3-R-gene late blight-resistant potato events with a novel procedure utilizing the Samplix Xdrop® enrichment technology - Zarka, Kelly A.; Jagd, Lea Møller; Douches, David S. (Frontiers in Plant Science, 2024)
Before commercialization of genetically modified crops, the events carrying the novel DNA must be thoroughly evaluated for agronomic, nutritional, and molecular characteristics. Over the years, Polymerase Chain Reaction-based methods, Southern blot, and short-read sequencing techniques have been utilized for collecting molecular characterization data. Multiple genomic applications are necessary to determine the insert location, flanking sequence analysis, characterization of the inserted DNA, and determination of any interruption of native genes. These techniques are time-consuming and labor-intensive, making it difficult to characterize multiple events. Current advances in sequencing technologies are enabling whole genomic sequencing of modified crops to obtain full molecular characterization. However, in polyploids, such as the tetraploid potato, it is a challenge to obtain whole genomic sequencing coverage that meets regulatory approval of the genetic modification. Here we describe an alternative to labor-intensive applications with a novel procedure using Samplix Xdrop® enrichment technology and next-generation Nanopore sequencing technology to more efficiently characterize the T-DNA insertions of four genetically modified potato events developed by the Feed the Future Global Biotech Potato Partnership: DIA_MSU_UB015, DIA_MSU_UB255, GRA_MSU_UG234 and GRA_MSU_UG265 (derived from regionally important varieties Diamant and Granola). This research will contribute to meeting regulatory safety and regulatory approval requirements for commercialization with small shareholder farmers in target countries within our partnership.